2003
DOI: 10.1002/art.10900
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic T cells in murine lupus exhibit spontaneous signaling activity through phosphatidylinositol 3‐kinase and mitogen‐activated protein kinase pathways

Abstract: Objective. To determine the activation status of two cytoplasmic signaling pathways, phosphatidylinositol 3-kinase (PI 3-kinase) and the mitogen-activated protein kinase (MAPK) family.Methods. We studied the pathogenic CD4؉ T cells that drive disease in the parent-into-F 1 mouse model of lupus-like chronic graft-versus-host disease (GVHD). We determined immunoprecipitated kinase activity for PI 3-kinase and MAPK members ( Results. Compared with negative controls, unfractionated splenocyte kinase activity from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
0
23
1
1
Order By: Relevance
“…Enhanced I A -PI3K activation causes lupus (3)(4)(5). Moreover, endogenous PI3K activation was observed in a graft-vs-host-induced murine systemic lupus model (20) and in lupus-prone MRL/lpr mice (21). Our preliminary data suggest that PI3K activity is also increased in human SLE T cells (Ͼ75% of patients, n ϭ 17, in progress).…”
Section: Discussionmentioning
confidence: 59%
“…Enhanced I A -PI3K activation causes lupus (3)(4)(5). Moreover, endogenous PI3K activation was observed in a graft-vs-host-induced murine systemic lupus model (20) and in lupus-prone MRL/lpr mice (21). Our preliminary data suggest that PI3K activity is also increased in human SLE T cells (Ͼ75% of patients, n ϭ 17, in progress).…”
Section: Discussionmentioning
confidence: 59%
“…To study T cells, short-term cultures were chosen over freshly isolated peripheral blood cells because T cells in SLE patients may be desensitized from repeated autoantigenic stimulation in vivo and from steroid therapy (32), whereas the activity of lupus T cells can reemerge after resting (33,34). Ficoll gradient-separated peripheral blood mononuclear cells (PBMCs) from patients with SLE and from healthy subjects were cultured under identical conditions at a concentration of 1 ϫ 10 6 /ml in 48-well plates in AIM-V (Invitrogen, Carlsbad, CA) with 20 units/ml IL-2, 10 ng/ml IL-7, and 10 ng/ml IL-15 (to prevent the death of memory T cells) (32).…”
Section: Methodsmentioning
confidence: 99%
“…These predictions warrant further experimental verification. Using the graft-versus-host disease model in which a disease resembling lupus is engineered in F1 recipients following injection of allomismatched parental T cells, Niculescu et al demonstrated strong upregulation of PI3K, p38 MAPK , and JNK-1 activity in donor CD4 + T cells (35). Increased spontaneous PI3K and JNK activity has also been documented in T cells from human SLE patients (35).…”
Section: Figurementioning
confidence: 99%
“…Using the graft-versus-host disease model in which a disease resembling lupus is engineered in F1 recipients following injection of allomismatched parental T cells, Niculescu et al demonstrated strong upregulation of PI3K, p38 MAPK , and JNK-1 activity in donor CD4 + T cells (35). Increased spontaneous PI3K and JNK activity has also been documented in T cells from human SLE patients (35). Rapoport et al demonstrated constitutive upregulation of the MAPKs in lymphocytes from SLE patients, associated with downregulation of early p21 Ras signaling (36).…”
Section: Figurementioning
confidence: 99%